The Classical Liberal Constitution: The Uncertain Quest for Limited Government - RICHARD A. EPSTEIN (Harvard University Press, 2014)
The Classical Liberal Constitution represents the culmination of my lifetime project of developing a distinctive synthesis of constitutional law that does not fall squarely within either the conservative or progressive camp. I started work on this volume in 2006, fi nished a fi rst draft in 2010, and have done extensive revision and expansion of the book to prepare it for publication in late 2013. At one level, my ambition has been to give a comprehensive account of how the various provisions of the United States Constitution, dealing as they do with both structural issues and individual rights, can best be explained in light of classical liberal theory. That theory in turn starts from the twin pillars of private property and limited government, and seeks to make sure that each and every government action improves the overall welfare of the individuals in the society it governs. It is no part of the theory to extol any version of philosophical egoism that allows any individual to do what he or she will no matter what the consequences to others. Classical liberalism is a social theory, not the magic paean of radical individualism with which it has often been confl ated, especially by its detractors on all sides of the political spectrum. In the course of my thinking on this subject, it became increasingly clear that an examination of constitutional law principles must start with the text of the Constitution. But that truism is not a full-throated endorsement of the strong modern defenses of constitutional originalism. The harder one probes, the more apparent it becomes that analysis must go quickly beyond that starting point in order to fi ll in the details of the larger picture of which the text is an indispensable part. In particular, the Constitution makes liberal use of such terms, taken in alphabetical order, as â€œcitizen,â€ â€œcommerce,â€ â€œcontract,â€ â€œcruel and unusual punishments,â€ â€œdue process,â€ â€œfreedom,â€ â€œgeneral welfare of the United States,â€ â€œjudicial power,â€ â€œlaw and equity,â€ â€œnecessary and proper,â€ â€œprivate property,â€ â€œreligion,â€ and many more. Yet at the same time the document, self-consciously, does not contain a glossary of what these vital terms mean. We know, however, that their use long antedates their inclusion in the Constitution, so that in a deep sense no one can understand how these terms operate without understanding their historical context in relation to both institutional arrangements and private transactions. Many of these terms have received extensive elaboration in private law disputes between ordinary persons. Others were in constant use in public law contexts prior to the drafting of the Constitution. A full analysis must take both these developments into account.